The other side - Banyai, Istvan (San Francisco : Chronicle Books, 2005)
A wordless picture book that shows a series of familiar scenes through many twists in point of view, such as a boy looking down out of a jet's window and another boy on the ground looking up at the same jet.
Keywords: Visual perception -- Fiction; Stories without words; Visual perception -- Pictorial works -- Juvenile fiction; Children's stories -- Pictorial works